Similarities and differences between the Atlas lingüístico de Cuba (ALCu) and the Atlas de identidades del español de Cuba (AIEC) (Islas, 2023)
Introduction: The paper presents the differences and similarities between the Atlas Lingüístico de Cuba (ALCu) (Linguistic Atlas of Cuba) and the Atlas de identidades del español de Cuba (AIECu) (Atlas of Identities of Spanish of Cuba), on which we have begun working. Likewise, the achievements and, as any human work, shortcomings of the ALCu were noted.Methods: In the new AIECu, these shortcomings of the initial enterprise will be corrected and a new transdisciplinary analysis is proposed, based on the Theory of Complexity. The sociolinguistic variables established in the ALCu will be taken into account; and race, economic level, personality and emotions of the informants will be added.Results: The Real and Subjective/Cognitive levels are differentiated as well. The following levels will be researched: segmental phonetics, prosody, lexical, morphosyntactic, gestures and sign situations.Conclusions: A new unit of analysis is proposed, the interactional speech act (ISA) considered as an emergent dynamic unit.
Keywords: linguistic geography; linguistic atlas; complexity theory; complexity dynamic systems; prosody; gesture